TINGKAT PARTISIPASI MASYARAKAT TERHADAP PROGRAM PUSPAGA BALAI RW UPAYA PENCEGAHAN KEKERASAN PEREMPUAN DAN ANAK DI KOTA SURABAYA - Putri Desi Andriani; Agus Prianto (Halu Oleo University, 2024)
Children are a state asset in the future as a generation that will carry the fate of the Indonesian nation. To make the country better and more advanced, it is very necessary to protect Indonesian children from acts of violence and realize gender equality because to bring about a better nation, we need golden generations who are intelligent in knowledge and morals, but in reality, the number of acts of violence against children and the majority of victims being female is always increasing. The Surabaya city government is committed to collaborating with DP3APPKB in carrying out responsive prevention of acts of violence against women and children, through the RW Hall Learning Center which aims to expand services to prevent acts of violence through psycho-educational outreach and counseling in every smallest environment, namely every RW. The method used is qualitative and presented descriptively. The results of this research show that the level of community participation is the main requirement in implementing the vision and mission of the Puspaga Balai Rw program.